Myocardial insult and arrhythmias after acute hemorrhage in horses. (5th March 2015) - Navas de Solis, Cristobal; Dallap Schaer, Barbara L.; Boston, Ray; Slack, JoAnn
Abstract Objective The objectives of this investigation were to: (1) Determine if acute hemorrhage is associated with increased plasma cardiac troponin I (cTnI) concentration or cardiac arrhythmias, (2) to describe the types of arrhythmias and their clinical course in horses following acute hemorrhage, (3) to determine the ability of clinical or clinicopathological variables to predict an increase in cTnI concentration and the presence of arrhythmias, and (4) to determine the associations of cTnI and cardiac arrhythmias with outcome. Design Prospective observational study. Setting Large animal veterinary teaching hospital. Animals Eleven client‐owned adult horses admitted for treatment of acute hemorrhage (HG) and 4 adult horses undergoing controlled blood collection (BDG). Methods Serial cTnI concentrations were measured and continuous ECGs were obtained from the HG and BDG groups. Statistical tests were used to determine associations among acute hemorrhage and plasma cTnI concentrations, the presence of cardiac arrhythmias, clinicopathologic data (heart rate [HR], packed cell volume [PCV], total plasma protein [TPP], plasma lactate, and plasma creatinine concentrations), and outcome. Results Plasma cTnI concentration and ECG were within reference intervals at all time points in the BDG. All horses in the HG had increased cTnI (ranging from 0.1–29.9 ng/mL). Arrhythmias were detected in 8 of these horses. There was an association between acute hemorrhage and increased cTnI (P = 0.004, ρ = 0.77), and the presence of arrhythmias (P = 0.026, ρ = 0.64). There were associations among plasma cTnI concentration and the presence of arrhythmias (P = 0.005), arrhythmias requiring treatment (P = 0.036), and poor outcome (P = 0.024). Conclusions Acute hemorrhage results in myocardial injury that can be detected by measuring cTnI concentration. Arrhythmias were frequent in hospitalized horses following acute hemorrhage.